PENGARUH TRANSFER PRICING, LEVERAGE, DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK - Muhammad Alif Fachriza (2022)
This study is a quantitative study that aims to determine the effect of transfer pricing, leverage, and the intensity of fixed assets on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This study uses secondary data in the form of financial reports obtained from the official website of the Indonesia Stock Exchange or the company's website. The sample in this study amounted to 36 manufacturing companies. The data analysis technique of this research uses multiple linear regression analysis with regression model test and classical assumption test using STATA program. The results of this study concluded that (1) transfer pricing has a significant positive effect on tax avoidance, (2) Leverage has no effect on tax avoidance, and (3) the intensity of fixed assets has a significant positive effect on tax avoidance.